Photocurable cyanate ester containing hybrid coatings by an anhydrous sol-gel technique - KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2012)
This work reports the synthesis and characterization of hybrid coatings obtained by UV curable anhydrous sol-gel process. Chemical structure of the products was confirmed using spectroscopic methods such as infrared and nuclear magnetic resonance spectroscopy. The properties of the hybrid coatings such as thermal and mechanical properties were investigated in detail by scanning electron microscope, thermogravimetric analysis, and mechanical measurement. Cure kinetics of the coating formulations was investigated by differential scanning photo-calorimetry (Photo-DSC). Cross cut adhesion, pendulum hardness, gloss, pencil hardness. MEK rub test were also performed to measure the coating performance of the hybrid coatings. The results indicate that the addition of the appropriate amount of CPM and sol-gel can effectively improve the thermal and mechanical properties. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Maleimide; Cyanate ester; Anhydrous sol-gel; Coating; Photo-DSC; RADICAL POLYMERIZATION; N-PHENYLMALEIMIDE; EPOXY-RESINS; MALEIMIDE; PHOTOPOLYMERIZATION; COMPOSITES; COPOLYMERS; STYRENE; SYSTEM